The Influence of Digital Literacy and Relative Advantage on E-Commerce Adoption through Digital Training and Mentoring among MSMEs in Jakarta - Sun Lilya, Sun Lilya; Pasaribu, Rina Djunita (International Journal of Science, Technology & Management, 2024)
The Micro, Small and Medium Enterprises (MSME) sector has an important role in driving the country's economic development. In order for MSMEs to remain competitive with the growth of digital technology, they must be able to adapt to digitalization. Utilizing an e-commerce platform can provide information about which products are selling best and which products are not selling well. This data can be used to make decisions about inventory management, marketing, and more. Only 13% of MSMEs that utilize technology use e-commerce. The adoption of digital e-commerce technology among MSMEs in Jakarta is still uneven. This research aims to determine the influence of digital literacy and relative benefits on the adoption of digital e-commerce technology for MSMEs in Jakarta with digital training and mentoring as mediating variables. This research method is causal quantitative by collecting data using an online questionnaire to 399 respondents. The analysis technique used in this research is Sem with the help of the Smart-PLS program. The research results show that digital literacy and relative benefits influence digital training and mentoring, but not the adoption of e-commerce platform technology. Meanwhile, digital training and mentoring influences the adoption of e-commerce platform technology. The mediation results show that digital training and mentoring play a full mediating role in the relationship between digital literacy and the relative benefits of adopting e-commerce platform technology.